The Effect of Firm Cash Flow on Investment Decision Moderated by Financial Constraint and Mispricing - Andewi Rokhmawati (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Riau, 2019)
This study aims to examine the effect of cash flows on investment decision that is moderated by financial constraint and mispricing. The population of the study was all listed-manufacturing firms in Indonesia from 2014 to 2016. Samples were chosen based on the availability of firms’ financial report covering the period of the study. By using moderated regression analysis where financial constraint and mispricing as moderating variables, the study concluded that financial constraint weakens the effect of cash flow on investment. Although lower financially constrained-firms have an opportunity to choose their source of funding, they prefer to finance their investment from an internal source of funding (from cash flows) due to lower risk. Furthermore, mispricing does not have a role as a moderating variable. In this condition, overvalued firms are indifferent from choosing the source of funding. Finally, when financial constraint and mispricing are signed as a moderating variable, they weaken the effect of cash flow on investment. It means that firms with lower financial constraint and overvaluation prefer to use external funding by issuing new common stocks because it provides a lower cost of capital.